The Efficacy of Telepsychiatry in Digital Mental Health Interventions for the General Population: A Comprehensive Review - Ash Shishodia (Journal of Psychiatry and Psychological Sciences, 2026)
Background Mental health disorders represent one of the leading causes of disability worldwide and continue to place substantial pressure on healthcare systems. Despite growing awareness of mental illness and increasing demand for services, significant barriers to psychiatric care remain, including workforce shortages, geographical inequities, financial constraints, and persistent stigma. Telepsychiatry, defined as the delivery of psychiatric services through telecommunications technologies, has emerged as a promising strategy to address these challenges. Although telepsychiatry has been utilized for several decades, its adoption accelerated dramatically during the COVID-19 pandemic, prompting renewed interest in its long-term role within mental healthcare systems. Objective This review examines the efficacy of telepsychiatry in digital mental health interventions for the general population, focusing on clinical outcomes, patient satisfaction, accessibility, economic implications, implementation barriers, and future directions. Methods A structured review of the literature was undertaken using major electronic databases, including PubMed, PsycINFO, Embase, Scopus, and Google Scholar. Studies published between 2010 and 2026 were examined. Priority was given to randomized controlled trials, cohort studies, systematic reviews, meta-analyses, and large observational investigations evaluating telepsychiatry interventions in community and general adult populations. Results The available evidence suggests that telepsychiatry produces clinical outcomes comparable to conventional face-to-face psychiatric care across a range of common mental health conditions, including depressive disorders, anxiety disorders, and stress-related disorders. High levels of patient satisfaction, improved access to specialist care, and potential reductions in healthcare costs have been consistently reported. Nevertheless, challenges relating to digital literacy, internet accessibility, privacy concerns, regulatory variation, and healthcare inequities remain important considerations. Conclusion Telepsychiatry has evolved from a supplementary service model into a fundamental component of contemporary mental healthcare delivery. Current evidence supports its effectiveness, acceptability, and scalability. Future success will depend upon addressing digital inequalities, strengthening regulatory frameworks, and integrating telepsychiatry into sustainable hybrid models of care.